Detection of toxins involved in foodborne diseases caused by Gram‐positive bacteria. Issue 4 (11th June 2020) - Rajkovic, Andreja; Jovanovic, Jelena; Monteiro, Silvia; Decleer, Marlies; Andjelkovic, Mirjana; Foubert, Astrid; Beloglazova, Natalia; Tsilla, Varvara; Sas, Benedikt; Madder, Annemieke; De Saeger, Sarah; Uyttendaele, Mieke
Abstract: Bacterial toxins are food safety hazards causing about 10% of all reported foodborne outbreaks in Europe. Pertinent to Gram‐positive pathogens, the most relevant toxins are emetic toxin and diarrheal enterotoxins of Bacillus cereus, neurotoxins of Clostridium botulinum, enterotoxin of Clostridium perfringens, and a family of enterotoxins produced by Staphylococcus aureus and some other staphylococci. These toxins are the most important virulence factors of respective foodborne pathogens and a primary cause of the related foodborne diseases. They are proteins or peptides that differ from each other in their size, structure, toxicity, toxicological end points, solubility, and stability, types of food matrix to which they are mostly related to. These differences influence the characteristics of required detection methods. Therefore, detection of these toxins in food samples, or detection of toxin production capacity in the bacterial isolate, remains one of the cornerstones of microbial food analysis and an essential tool in understanding the relevant properties of these toxins. Advanced research has led into new insights of the incidence of toxins, mechanisms of their production, their physicochemical properties, and their toxicological mode of action and dose‐response profile. This review focuses on biological, immunological, mass spectrometry, and molecular assays as the most commonly used detection and quantification methods for toxins of B. cereus, C. botulinum, C. perfringens, and S. aureus . Gathered and analyzed information provides a comprehensive blueprint of the existing knowledge on the principles of these assays, their application in food safety, limits of detection and quantification, matrices in which they are applicable, and type of information they provide to the user.